TECHNIQUES OF REHABILITATIVE TREATMENT OF CHILDREN WITH A VARIETY OF DISEASES ARE PRESENTED - Islam M. Uzdenov (Вестник Северо-Кавказского федерального университета)
The article discusses the factors affecting the health of children in schooling. The examples of health monitoring and disease risk factors in children are given.